Adopting Artificial Intelligence in Power Stations - Kumar Dash, Sujit; Narayan Mohanty, Mihir (International Journal of Psychosocial Rehabilitation, 2025)
Power station acts as a source of supplying power to the households which is considered to be reliable. The use of power station has grown increasing based on the location, new technology developed by new generation, transmitting and distributing the energy. Artificial Intelligence has promised to solve the problems related to power station like forecasting, controlling and planning, etc. The advancements in this field helps in dealing with issues faced by the applications related to huge power generating stations with more connections so as to meet the increasing demand in the load. The application is successful in different fields related to power system engineering.